2018
DOI: 10.3389/fvets.2018.00254
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Gut Microbiota: Importance and Detection Technology

Abstract: Sustainable poultry meat and egg production is important to provide safe and quality protein sources in human nutrition worldwide. The gastrointestinal (GI) tract of chickens harbor a diverse and complex microbiota that plays a vital role in digestion and absorption of nutrients, immune system development and pathogen exclusion. However, the integrity, functionality, and health of the chicken gut depends on many factors including the environment, feed, and the GI microbiota. The symbiotic interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
292
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(317 citation statements)
references
References 94 publications
16
292
0
9
Order By: Relevance
“…The emergence of cheaper DNA sequencing technologies [17,18] has led to an explosion in studies which have sought to characterise the chicken gastrointestinal microbiota, particularly using 16S rRNA gene-based methods. Using this methodology, it has been found that the chicken caecal microbiota in the first few weeks of life is predominantly colonised by members of the Firmicutes, mostly of the order Clostridiales [8,19]. While valuable, marker-gene studies do not enable an in-depth functional and genomic characterisation of the microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of cheaper DNA sequencing technologies [17,18] has led to an explosion in studies which have sought to characterise the chicken gastrointestinal microbiota, particularly using 16S rRNA gene-based methods. Using this methodology, it has been found that the chicken caecal microbiota in the first few weeks of life is predominantly colonised by members of the Firmicutes, mostly of the order Clostridiales [8,19]. While valuable, marker-gene studies do not enable an in-depth functional and genomic characterisation of the microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of cheaper DNA sequencing technologies (17, 18) has led to an explosion in studies which have sought to characterise the chicken gastrointestinal microbiota, particularly using 16S rRNA gene based methods. Using this methodology, it has been found that the chicken caecal microbiota in the first few weeks of life is predominantly colonised by members of the Firmicutes , mostly of the order Clostridiales (8, 19). Whilst valuable, marker-gene studies do not enable an in-depth functional and genomic characterisation of the microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in sequencing technologies have led to a better understanding of the microbiota of many livestock species [1][2][3][4], leading some to suggest that we could optimise the composition of microbiota in these economically important animals to improve production and sustainability [5]. However, to do so would require a good understanding of the types of microbes which naturally occur in these animals and the role they play in nutrition and health.…”
Section: Introductionmentioning
confidence: 99%